Mastering of written language as one of the conditions of transition from pre-conceptional to conceptional thinking - Garbačiauskienė , M.; Grigaitė , B. (Psichologija, 1980)
In the theoretical part of the article some investigations of transition from pre-conceptional to conceptional thinking are analysed, views of different authors (J. Piaget, L. Vigotsky, J. Bruner, etc.) on the conditions of such a transition are discussed. The influence of the language, especially written, on the development of conceptional thinking is ascertained. In the other part of the article the results of the experiment are presented. It is stated that pupils begin to differ signs of written language from similar geometrical figures rather early (at 4-5 years of age), they can use them as a means of easement of classification. Statistically important connection between mastering of written language and displacement in pupils thinking (disappearance of "Piaget's phenomena") has been determined in experimental preparatory for school groups of kindergartens.
Keywords: J. Piaget; L. Vygotsky; J. Bruner; written language; conceptional thinking